NON-SURGICAL TREATMENT PROGNOSIS FOR LARYNGEAL CANCER BASED ON AMERICAN JOINT COMMITTEE ON CANCER STAGING AND T AND N INTEGER SCORE - Larizadeh, Mohammad Hasan; Ahmad Naghibzadeh-Tahami,; Eslami, Hadi (Journal of Ayub Medical College Abbottabad, 2023)
Background: The American Joint Committee on Cancer (AJCC) system is the most acceptable staging method. In this study, an attempt has been made to evaluate the survival rate of laryngeal cancer based on the AJCC and T and N integer scores (TANIS). Methods: In this prospective cohort study, from March 2004 to March 2021, laryngeal cancer patients who were considered for non-surgical treatment were included.Ù…Ø¹ÛŒØ§Ø±Ù‡Ø§ÛŒ Ø®Ø±ÙˆØ¬: Ù…ØªØ§Ø³ØªØ§Ø²ØŒ Ø¹Ø¯Ù… ØªØÙ…Ù„ Ù¾Ø±ÙˆØªÚ©Ù„ Ù…Ø·Ø§Ù„Ø¹Ù‡ØŒ Ø¯Ø±Ù…Ø§Ù† Ù†Ø§Ù‚Øµ Ø¨Ù‡ Ù‡Ø± Ø¯Ù„ÛŒÙ„ ÛŒØ§ Ø¬Ø±Ø§ØÛŒ Ù‚Ø¨Ù„ÛŒ Ø¶Ø§ÛŒØ¹Ù‡ Exclusion criteria were: metastasis, intolerance to the study protocol, incomplete treatment for any reason, or previous surgery on the lesion. Ù…Ø¹ÛŒØ§Ø±Ù‡Ø§ÛŒ Ø®Ø±ÙˆØ¬ Ø¹Ø¨Ø§Ø±Øª Ø¨ÙˆØ¯Ù†Ø¯ Ø§Ø²: Ù…ØªØ§Ø³ØªØ§Ø²ØŒ Ø¹Ø¯Ù… ØªØÙ…Ù„ Ù¾Ø±ÙˆØªÚ©Ù„ Ù…Ø·Ø§Ù„Ø¹Ù‡ØŒ Ø¯Ø±Ù…Ø§Ù† Ù†Ø§Ù‚Øµ Ø¨Ù‡ Ù‡Ø± Ø¯Ù„ÛŒÙ„ ÛŒØ§ Ø¬Ø±Ø§ØÛŒ Ù‚Ø¨Ù„ÛŒ Ø±ÙˆÛŒ Ø¶Ø§ÛŒØ¹Ù‡. «Ù†ØªØ§ÛŒØ¬ Ú©Ø§Ù…Ù„» Ø¨Ø§Ø± Ù†Ø´Ø¯ Ø§Ù…ØªØØ§Ù† Ù…Ø¬Ø¯Ø¯ Ø¯Ø±ØØ§Ù„ ØªÙ„Ø§Ø´ Ù…Ø¬Ø¯Ø¯... Ø¯Ø±ØØ§Ù„ ØªÙ„Ø§Ø´ Ù…Ø¬Ø¯Ø¯... Radiation alone was considered for T1-T2 lesions without nodal involvement. Sequential or concomitant chemoradiation (based on physician choice) was considered for locoregionally advanced patients (T3/T4 or node positive). The 2-year, 5-year and 10-year overall survival (OS) and progression-free survival (PFS) rates were estimated using Kaplan-Meier method. Cox -Regression method was used for covariates analysis. Results: The 2-year, 5-year and 10-year overall survival (OS) rates in all patients were estimated to be 82%, 70% and 41%, respectively. The 2-year, 5-year and 10-year progression-free survival (PFS) rates in all patients were estimated to be 78%, 59% and 41%, respectively. The 5-year OS rates for stages I, II, III, IVa, and IVb were 83, 84, 51, 12, and 19 percent, respectively. The 5-year OS rates for TANIS 1, 2, and 3 were 85, 62 and 53 percent, respectively. Based on multivariate analysis, the group stage (p=0.001), TANIS group (p=0.003) and tumour subsite. (p=0.006) were independently effective in survival rates. Conclusion: TANIS-3 can simply predict prognosis of non- surgically treated laryngeal cancers. The separation of different prognostic groups by TANIS is better than the AJCC system. More extensive studies are necessary to confirm this.